2019
DOI: 10.25026/jsk.v2i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Physical Characterization of Onion (Allium ascalonicum L) Bulb Extract in Cream Using Tween 80 and Span 60 as the Emulgator

Abstract: In Indonesia, it is not uncommon to find children who suffer from fever which can occur due to the change of weather from the rainy season during the dry season or vice versa. Communities in rural areas generally use onion (Allium ascalonicum L) to relieve fever in children. Cream preparations are made by varying the concentration of the emulgator to determine the effect of different concentrations of the emulgator on the physical characteristics of the cream preparation. The emulgator used is tween 80 and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Cream-type testing was performed by using the dilution method, which was by diluting the cream sample in distilled water. Cream that dissolves when diluted with distilled water is included in the m/a type, while cream that does not dissolve belongs to the a/m type [24]. In the cream type test, it was observed that the cream sample dissolved in distilled water, so it can be concluded that this sunscreen cream has a m/a type.…”
Section: Cream-type Testmentioning
confidence: 99%
“…Cream-type testing was performed by using the dilution method, which was by diluting the cream sample in distilled water. Cream that dissolves when diluted with distilled water is included in the m/a type, while cream that does not dissolve belongs to the a/m type [24]. In the cream type test, it was observed that the cream sample dissolved in distilled water, so it can be concluded that this sunscreen cream has a m/a type.…”
Section: Cream-type Testmentioning
confidence: 99%